2015
DOI: 10.1093/europace/euv300
|View full text |Cite
|
Sign up to set email alerts
|

Brugada syndrome: clinical presentation and genotype—correlation with magnetic resonance imaging parameters

Abstract: Brugada syndrome patients with an SCN5A mutation reveal distinct changes in RV volumes and function when compared with those without an SCN5A mutation. Furthermore, mutation-positive patients have a higher likelihood of a spontaneous type 1 BrS-ECG, which is associated with a higher incidence of clinical events. Cardiovascular magnetic resonance may provide additional insight to distinguish between SCN5A mutation-positive and -negative BrS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
2
29
2
1
Order By: Relevance
“…In patients with the SCN5A mutation, morphologic and functional changes are observed in cardiovascular MRI, including larger right ventricular (RV) vol-umes and lower RV ejection fraction. This may indicate a more severe phenotype in this group of patients in comparison to those without the SCN5A mutation or controls [8]. These findings are in line with those of Catalano et al, who observed that in their group of BrS patients, 33% presented with the spontaneous type 1 BrS ECG pattern and 30% with an identified SCN5A mutation [9].…”
Section: Utility Of Cardiac Imaging In Brssupporting
confidence: 91%
See 1 more Smart Citation
“…In patients with the SCN5A mutation, morphologic and functional changes are observed in cardiovascular MRI, including larger right ventricular (RV) vol-umes and lower RV ejection fraction. This may indicate a more severe phenotype in this group of patients in comparison to those without the SCN5A mutation or controls [8]. These findings are in line with those of Catalano et al, who observed that in their group of BrS patients, 33% presented with the spontaneous type 1 BrS ECG pattern and 30% with an identified SCN5A mutation [9].…”
Section: Utility Of Cardiac Imaging In Brssupporting
confidence: 91%
“…In a multivariate analysis, Rudic et al showed that reduced right ventricular ejection fraction (RVEF) and increased right ventricular end-diastolic volume index (RVEDVi) were associated with a history of syncope or aborted SCA at the time of BrS diagnosis [8].…”
Section: Risk Assessment In Brugada Syndromementioning
confidence: 99%
“…negative BrS patients and healthy subjects. (16,17) In non-ischemic cardiomyopathies including dilated cardiomyopathy and hypertrophic cardiomyopathy, arrhythmogenesis has been associated with presence of late gadolinium enhancement (LGE) representing focal myocardial fibrosis on CMR. (18,19) Systematic assessment for myocardial fibrosis in BrS has not been performed and therefore we sought to characterise a cohort of patients using the CMR LGE technique.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, since SCN5A is expressed throughout the atria and ventricles, LoF mutations are expected to cause both atrial and ventricular conduction slowing and thus PR and QRS prolongation (van Weerd & Christoffels, ). Apart from these electrocardiographic differences, MRI studies have shown that SCN5A mutation carriers also have subtle morphological differences compared to SCN5A ‐negative BrS patients (van Hoorn et al., ; Rudic et al., ).…”
Section: Discussionmentioning
confidence: 99%